PERAN NABI IBRAHIM SEBAGAI AYAH (Penggunaan Metode Maudhu'i Dalam Menafsirkan Al-Qur'an) - Andi Raita Umairah Syarif (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
This article looks at the role of Prophet Ibrahim as a father, using the Maudhu'i method the author will explain some of the views of the scholars regarding the interpretation of the role of Prophet Abraham as a father. This method wants to see how Allah's demands on Prophet Abraham are so that they can form the character of their Son who is so obedient to God and his parents. This provides a general description of how the pattern of educating children. So that readers can take the lessons in this article how to raise good children according to Islamic teachings. In conclusion, there are several ways to educate children including placing them in a good environment.